Importance of Illness Acceptance Among Other Factors Affecting Quality of Life in Acromegaly - Jawiarczyk-Przybyłowska, Aleksandra; Szcześniak, Dorota; Ciułkowicz, Marta; Bolanowski, Marek; Rymaszewska, Joanna (Frontiers in Endocrinology, 2020)
Introduction: The aim of this study was to analyze psychological factors of patients with acromegaly and assessment of their relationship with the quality of life (QoL) in the context of the control of the disease. Material and methods: A total sample of 50 patients (62% of females; mean age=51.6614.5) with acromegaly underwent a comparative, cross-sectional cohort assessment including the QoL (AcroQoL, WHOQoL-BREF), psychiatric morbidity (GHQ-28), the acceptance of illness (AIS) as well as influence of treatment, comorbidities and symptoms in the relation of disease activity. Acromegaly group was divided in two subgroups: patients with uncontrolled acromegaly (UA, n= 28) and patients with controlled acromegaly (CA, n=22). Results: The acromegaly groups did not differ in health-related QoL measured with AcroQoL and WHOQoL questionnaires. However, obtained results showed QoL impairments in all subscales and the study participants had decreased scores compared to reference values. The interaction of the relationship between the AIS and disease activity as well as the prevalence of all psychopathological symptoms and disease activity were tested and the statistically significantly differences in the context of QoL in AcroQoL questionnaires and its domains were observed in relation to the course of the disease. No difference in acromegaly symptoms as well as in number of comorbidities were found between CA and UA but these two parameters affected the results QoL scores in AcroQol questionnaires and their domains, regardless the disease activity. Similarly, the prevalence of psychopathological symptoms (GHQ-28) contributed the level of acceptance of the disease, regardless the disease activity. The strongest predictors of QoL were related to the level of illness acceptance (p=0.01) as well as serum growth hormone concentration. Conclusion: Minding people with UA, the control of biochemical factors seemed to be more important for the quality of life perception, while among CA, psychological variables such as AIS are observed to play a fundamental role in QoL. Moreover, inclusion of patient’s acceptance of the illness into clinical routine would promote holistic, patient-centered care and empower doctor-patient partnership where patients’ expectations and perceptions are constantly tracked. Obtaining biochemical control should not be considered as the only measure of treatment success.